Sekolah Luar Biasa Autis Boyolali Berbasis Alam Dengan Penekanan Taman Terapi - Wahyuni, Endang; , Dr. Ir. Dhani Mutiari, MT; , Rini Hidayati, ST, MT (2015)
Chidren are the future generation, therefore every child receives a proper education for a better future, for normal children and children with special needs such as children with autism. Autistic children divited into two autistic hyperactive and hypoactive. Children with special needs get different facilities with other normal children, because in addition to learning the special treatment is necessary. Schools not only serves as a means of academic education using books as the window of science, but also can open space as a learning method and fun play therapy. Children more easly understand everything directly into the environment. Autism School Boyolali in a school-based nature with emphasis on therapy as a means of healing garden which aims to shape the character of the child and the creativity talents. The methods used in these school is children freedom to explore and get to know nature. School children are also taught how to hone their skills in entrepreneurship as they are trained how to grow good and true such as vegetables, flowers, fruits, etc. and then the harvest will be sold to local residents, in addition they are also trained how to utilize waste that still can be recycled. Proceeds from the sale will be saved to the needs of children during school, the learning activities can be implemented in the long term. Therapeutic activies more done in open space by distinguishing between hyperactive and hypoactive therapy area, because they are different sensory needs. Garden design adapted to its function which garden visual theraphy, tactile and vestibular. One of problems in individuals with autism is a sensory disorder that causes the child's sensory system fails to respond and not adaptive to the environment. Some treatments can help children's sensory systems, but these therapies are mostly taken place indoors, yet not many take advantage of the outdoor space. In fact, according to some researchers, the outdoor space has positive effects on the development of children, including children with special needs, as well as lower levels of stress a person. Analysis process is done by a primary method, whereas the design concept generated through a secondary method make difference in the selection of both hardscape and softscape material, physical form, elements, and garden features. In addition to differences in zoning, the form of both areas is also affected. For an example, visually, hypersensitive area is formed from circular/curved elements, while the hyposensitive area is formed from firm and segmental elements.